Organization and Function of Non-dynamic Biomolecular Condensates. Issue 2 (February 2018) - Woodruff, Jeffrey B.; Hyman, Anthony A.; Boke, Elvan
Abstract : Cells compartmentalize biochemical reactions using organelles. Organelles can be either membrane-bound compartments or supramolecular assemblies of protein and ribonucleic acid known as 'biomolecular condensates'. Biomolecular condensates, such as nucleoli and germ granules, have been described as liquid like, as they have the ability to fuse, flow, and undergo fission. Recent experiments have revealed that some liquid-like condensates can mature over time to form stable gels. In other cases, biomolecular condensates solidify into amyloid-like fibers. Here we discuss the assembly, organization, and physiological roles of these more stable condensates in cells, focusing on Balbiani bodies, centrosomes, nuclear pores, and amyloid bodies. We discuss how the material properties of these condensates can be explained by the principles of liquid–liquid phase separation and maturation. Highlights: Biomolecular condensates are membrane-less organelles that form through phase separation of scaffolding proteins. Biomolecular condensates can exhibit a broad spectrum of material properties, from dynamic liquid-like droplets to non-dynamic gels and solid amyloids. In vitro reconstitution suggests that non-dynamic condensates can start as liquid droplets that rapidly solidify. Bioreactive gels are condensates that promote biochemical reactions, while functional amyloids shut down biochemical reactions and promote cellular dormancy.